(The effectiveness of a proposed program based on future thinking skills in the collection of geography for fifth grade literary students) (Journal of the College of Basic Education, 2023)
It is the current study to identify the effectiveness of a proposed program based on future thinking skills in achieving its geographical subject and mental flexibility among students of the fifth literary class. In order to verify this, the researcher formulated the following zero assumptions: To achieve the aims of the research, the research community was chosen from the fifth preparatory grade students for the second year of Karkh Education Directorate for the academic year (2018-2019). The number of students reached (38) students. A student of the experimental group, the other formed (of the experimental group) and the other consisted of (33) of the control and to ensure the internal integrity of the experiment towards two categories of groups with variables (chronological age, previous achievement, previous knowledge, intelligence (Achievement test) was prepared from (50) items of multiple choice type to measure the levels of Bloom's classification (knowledge, understanding, application, analysis, synthesis, evaluation) and its validity and reliability were verified and the difficulty and distinction factor was extracted and applied to two research groups the researcher used an equation T-test for two independent samples, and the results showed that the experimental group that studied according to the program was superior to the control group that was studied according to the traditional method.